Social feedback processing from early to late adolescence: influence of sex, age, and attachment style. Issue 5 (23rd July 2014) - Vrtička, Pascal; Sander, David; Anderson, Brittany; Badoud, Deborah; Eliez, Stephan; Debbané, Martin
<x xml:space="preserve">Abstract</x> In this functional magnetic resonance imaging (fMRI) study, we looked at brain activity during social feedback processing in 33 healthy adolescents, aged 12 to 19 years. Besides investigating neural activation changes related to participant age and sex, we also assessed the influence of individual differences in attachment style. <boxed-text content-type="graphic" id="brb3251-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>